Endoscopic balloon dilation with steroid injection versus radial incision and cutting with steroid injection for refractory esophageal anastomotic stricture: a randomized study - Aoyama, Ikuo; Takizawa, Kohei; Kataoka, Kozo; Ogawa, Gakuto; Sano, Yusuke; Yamamoto, Yoshinobu; Tanaka, Tsutomu; Setoyama, Takeshi; Kadota, Tomohiro; Saito, Yutaka; Nagami, Yasuaki; Hikichi, Takuto; Nagata, Shinji; Urabe, Yuji; Ono, Hiroyuki; Doyama, Hisashi; Nagino, Ko; Tomita, Toshihiko; Tamaoki, Masashi; Ohno, Kazuya; Kobayashi, Masaaki; Abe, Seiichiro; Yano, Tomonori; Muto, Manabu (Endoscopy, 2025)
Esophageal stricture causes severe distress to patients; however, there are no established treatments for esophageal anastomotic strictures refractory to endoscopic balloon dilation (EBD). Steroid injection added to EBD and radial incision and cutting (RIC) are effective for such strictures, but it is unclear which is more effective. The objective of this study was to investigate the safety and efficacy of RIC plus steroid injection compared with EBD plus steroid injection for patients with refractory anastomotic strictures after esophagectomy.This was a multicenter, randomized phase II/III trial. Patients with esophageal anastomotic strictures refractory to three or more dilations were eligible. The primary endpoint in phase II was the proportion of predefined grade 3/4 adverse events (AEs). The co-primary endpoints in phase III were restricture-free survival and number of EBDs in the 24 weeks after treatment.130 patients were enrolled, with a dysphagia score of grade 2 in 104 patients (80.0%). The median number of dilations before registration was five in each arm. Predefined grade 3/4 AEs occurred in two patients (3.1%) in each arm. Restricture-free survival was 10.6 weeks (95%CI 6.9–20.1 weeks) with EBD and 8.7 weeks (95%CI 7.1–10.9 weeks) with RIC (one-sided P=0.82). The median number of EBDs in the 24 weeks after initial treatment was one (interquartile range [IQR] 0–2) for EBD and two (IQR 0–3) for RIC (one-sided P=0.99).EBD combined with steroid injection is the standard treatment for refractory anastomotic stricture after esophagectomy.